Optimisation of microwave-assisted pectin extraction from cocoa pod husk using response surface methodology - Abd Halim, Alyaa Nurathirah; Abd Gani, Siti Salwa; Halmi, Mohd Izuan Effendi; Abdul Wahab, Norliza (Universiti Putra Malaysia Press, 2026)
Managing the proper disposal of cocoa pod waste after beans are extracted is a very challenging process. Effective waste management requires a well-planned strategy to protect the environment from pollution, minimise disposal costs, and reduce hazardous waste. Furthermore, this study could help in turning agricultural waste into valuable products. Thus, this research aimed to extract pectin from cocoa pod fruits. The method of using microwave-assisted extraction (MAE) technique and citric acid as selected solvent extraction, as demonstrated by response surface methodology (RSM) at pH 1, 600 watts of microwave power at 5 minutes irradiation time, gave the highest yield (14.97% wt/wt). This MAE method shows great evidence in providing a high yield compared to the traditional methods. The results of DE of cocoa pectin range from 43.67-45.84%, indicating low methoxyl pectin. Low methoxyl pectin is below 50% of DE. Pectin yield (14.1% wt/wt) was achieved at optimised pH 1 conditions at 5 minutes of irradiation time at 500 watts of microwave power. The obtained results of FTIR have confirmed that the extracted polysaccharide of this current study was found to be pectin.